Challenges of the Tactical Leader in the Context of Multinational Military Operations Process - Robert-Marian Alixandrescu (Vojenské rozhledy)
This study explores the main challenges faced by leaders within the multinational military operations process. Based on the aspects addressed in the literature review, the questionnaire survey method will be applied to a representative sample of military personnel who had participated in various multinational activities, as tactical leaders. The findings reveal that the most significant challenges perceived by leaders include linguistic barriers, command and control (C2) issues, and differences in training, endowment, and doctrine, with planning identified as the most challenging operational phase. Statistical analysis further indicates that experienced leaders perceive these challenges more acutely, and the study outlines key solutions proposed by respondents, such as developing language skills, enhancing interoperability, and fostering adaptability as essential traits for overcoming difficulties in multinational military operations.